2015
DOI: 10.1103/physrevc.92.035202
|View full text |Cite
|
Sign up to set email alerts
|

Neutral pion photoproduction on the nucleon in a chiral quark model

Abstract: A chiral quark-model approach is adopted to study the γp → π 0 p and γn → π 0 n reactions. Good descriptions of the total and differential cross sections and single-polarization observables are obtained from the pion production threshold up to the second resonance region. It is found that (i) the n = 0 shell resonance ∆(1232)P 33 , the n = 1 shell resonances N(1535)S 11 and N(1520)D 13 , and the n = 2 shell resonance N(1720)P 13 play crucial roles in these two processes. They are responsible for the first, sec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
34
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 113 publications
11
34
0
Order By: Relevance
“…It is found that the main resonance masses and widths extracted by us are in good agreement with the world average values from PDG [2]. One point should be emphasized that our global fits of the π − p → ηn, K 0 Λ reaction data seem to favour a broad width Γ ≃ 400 MeV for N(1720)P 13 , however, this width is much broader than Γ ≃ 120 MeV extracted from the neutral pion photoproduction processes in our previous work [49]. A similar narrow width of N(1720)P 13 was also found by the CLAS Collaboration in the reaction ep → ep ′ π + π − [81].…”
Section: A Parameterssupporting
confidence: 87%
See 4 more Smart Citations
“…It is found that the main resonance masses and widths extracted by us are in good agreement with the world average values from PDG [2]. One point should be emphasized that our global fits of the π − p → ηn, K 0 Λ reaction data seem to favour a broad width Γ ≃ 400 MeV for N(1720)P 13 , however, this width is much broader than Γ ≃ 120 MeV extracted from the neutral pion photoproduction processes in our previous work [49]. A similar narrow width of N(1720)P 13 was also found by the CLAS Collaboration in the reaction ep → ep ′ π + π − [81].…”
Section: A Parameterssupporting
confidence: 87%
“…In the SU(6)⊗O(3) symmetry limit, the contributions of N(1650)S 11 should be forbidden in the π − p → K 0 Λ reaction due to the Moorhouse selection rule [73,74]. The obvious evidence of N(1650)S 11 in the π − p → K 0 Λ reaction further confirms that the SU(6)⊗O(3) symmetry is broken, and the configuration mixing between N(1535)S 11 and N(1650)S 11 should be necessary as suggested in our previous studies of the meson photoproduction processes [48,49].…”
Section: A Parameterssupporting
confidence: 65%
See 3 more Smart Citations